Incidence Rate and Clinical Characteristics of Pterygium in Rumah Sakit Khusus Mata Masyarakat, South Sumatra Province - Alma Putri Andani; Desi Oktariana; Ibrahim Ibrahim (Fakultas Kedokteran Universitas Riau, 2026)
Pterygium grows widely in tropical regions. Consequently, Indonesia has a comparatively high incidence rate of pterygium. On the other hand, South Sumatera has the least amount of data collected about the incidence rate and clinical characteristics of pterygium. The purpose of this study was to ascertain the incidence rate and clinical characteristics of pterygium patients in Rumah Sakit Khusus Mata Masyarakat in South Sumatera Province from 2019 to 2022. Descriptive observational methods with retrospective cohort study were employed in this investigation. Using a purposive sampling strategy, the sample consisted of patients with pterygium identified from the medical records. The incidence rate of pterygium among patients of RS Khusus Mata Masyarakat was 0.023 (2.3%) or 23 cases/1000 people per year. The 152 pterygium patients included in this study were mostly female (59.9%), mostly between the ages of 61 and 70 (33.6%), and most of them worked indoors (65.1%). Most patients' visual acuity (VA) was 6/9 (15.8%). The location of pterygium was primarily nasal (87.2%), grade II (32.5%), unilateral lateralization (61.2%), clinical manifestation of foreign body sensation (45.1%), and astigmatism (29%). Pterygium was mainly found in females, 61-70 years old, having an indoor job, 6/9 VA, nasal location, grade II, unilateral lateralization, the clinical manifestation of foreign body, and having less astigmatism.